INNV-39. THE IMPACT OF MULTIDISCIPLINARY MANAGEMENT ON THE OVERALL SURVIVAL OF GLIOBLASTOMA AND ANAPLASTIC GLIOMA PATIENTS IN THE ERA OF PRECISION MEDICINE-A COMMUNITY PHYSICIAN'S EXPERIENCE AND DILEMMA. (11th November 2019) - Ranjan, Tulika; Yu, Alexander; Wegner, Rodney; Karlovits, Stephen; Xu, Linda; Hameed, Muhammad
Abstract: The newer modalities of GBM treatment on the horizon are targeted therapy utilizing precision medicine, immunotherapy, Laser interstitial thermal therapy (LITT), ChemoID, CAR-T cell therapy, etc. There is always dilemma about referring a patient to the clinical trials which restrict the patient to one therapeutic agent Vs using a multi-disciplinary approach to improve patient's survival. We present a single- institution retrospective data of the multidisciplinary management of our high grade glioma patients and their outcome. A chart review is being performed on high grade glioma patients (GBM, Gliosarcoma, Anaplastic Astrocytomas and Anaplastic Oligodendrogliomas) who had genomic alterations identified by commercial next generation sequencing. Thus far 100 patients had molecular profiling done at our institution and precision medicine was implemented in >50 patients along with other treatments. Of 100 patients 82 were GBM and 18 were Anaplastic gliomas. There were 61 males and 39 females. MGMT methylation was seen in 36 patients and 12 patients had IDH1 mutation. The actionable mutations seen EGFR, EGFRvIII, TERT, PDGFR, CDKN2A-20, BRAF, PTEN, NF1- PD/PD-L1. The targeted therapy used were imatinib, sirolimus, afinotor, debrfenib, pembrolizumab, EGFR vIII vaccine. The chemotherapies utilized were BCNU, CCNU, CPT-11, Etoposide, carboplatin. Of 100 high grade glioma patients 8 patients underwent LITT, 24 patients received SRS, 58 patients received Avastin. All patients are being followed for overall survival (OS) and progression free survival (PFS-6) at this point. Of the 82 GBM patients 35 are still alive at a median 21 months. The median overall survival of the 47 dead GBM patients was 24 months. CONCLUSION: In high grade Glioma patients a multi-disciplinary approach may prolong the survival and the genomic analysis does impact the outcome of these patients. When we implement more than one therapy at the same time overall survival can't be credited to one specific mode of therapy.